Upaya Meningkatkan Motivasi Belajar dan Keterampilan Menulis Permulaan Melalui Penerapan Model Pembelajaran Kontekstual Pada Siswa Kelas II SD Negeri 5 Karangasem - Made Ayu Citra Widiastuti (Jayapangus Press, 2021)
This study aims to improve learning motivation and initial writing skills of second grade students of SD Negeri 5 Karangasem in the even semester of the 2017/2018 school year. To achieve this goal, action research was carried out in two learning cycles with 20 students as research subjects. The object of research is the application of the Contextual learning model to improve motivation and initial writing skills. The data analysis used in this research is descriptive analysis. The results of data analysis showed that: 1) The application of contextual learning models can increase the learning motivation of second grade students of SD Negeri 5 Karangasem in the even semester of the 2017/2018 academic year. This result can be seen from the motivation data of 77.90 in the first cycle with moderate qualifications and in the second cycle it increases to 83.8 with high qualifications. 2) The application of contextual learning models can improve Beginning Writing Skills in Grade II Students of SD Negeri 5 Karangasem Even Semester of the 2017/2018 Academic Year. This result can be seen from the student's average score of 63.5 in the first cycle with 75% classical completeness, and in the second cycle it increases to an average value of 75.5 with 100% completeness. Thus, the motivation and initial writing skills of second grade students at SDN 5 Karangasem can be improved through the application of the Contextual learning model.